Expansions, quality, and affirmative action in public higher education institutions - Connie Bayudan-Dacuycuy; Christopher Cabuay; Paola Ellaine D. Luzon (Philippine Institute for Development Studies (PIDS), 2024)
Public higher education institutions in the Philippines have experienced expansions in campuses, programs, and enrollments. Alongside these expansions are challenges that can limit the public higher education institutions' capacity to deliver quality education and ensure the disadvantaged groups' access to tertiary education. This study analyzes the nature of expansions in state and local universities and colleges, identifies issues and challenges with these expansions, and provides policy recommendations to ensure that expansions in public higher education institutions occur with commensurate measures that safeguard the quality of educational products and services while guaranteeing affirmative action.
Keywords: 330; expansion in public HEIs; affirmative action; access; quality; LUCs